Protective effects of resveratrol on the ethanol‐induced disruption of retinogenesis in pluripotent stem cell‐derived organoids. Issue 5 (30th March 2023) - Li, Hongyu; Gao, Lixiong; Ye, Zi; Du, Jinlin; Li, Wen; Liang, Liqing; Zeng, Quan; Xi, Jiafei; Yue, Wen; Li, Zhaohui
Abstract : Prenatal alcohol exposure‐induced fetal alcohol syndrome (FAS) can lead to serious maldevelopment in many organ systems, including the eyes. In the present study, the effects of alcohol exposure on early development of the human retina and the therapeutic effects of resveratrol on alcohol‐induced neural retinal damage were observed for the first time in an in vitro retinal organoid model. We report that the number of proliferating and apoptotic cells decreased and increased, respectively, following ethanol treatment. In addition, the number of PAX6 + cells and migrating TUJ1 + cells decreased after ethanol exposure. However, pretreatment with resveratrol prevented all of these negative effects. Using RNA sequencing and immunofluorescence, we identified activation of the PI3K‐AKT signalling pathway as the possible mechanism through which resveratrol protects the retina from alcohol‐induced damage. These results suggest that while ethanol exposure can restrict the growth of the human retina and impede the development of specific retinal cells, pretreatment with resveratrol may be a feasible method for preventing these effects. Abstract : Pluripotent stem cell‐derived organoids in vitro can be widely used in disease modelling and drug screening. Based on a retinal organoid model, we found that alcohol significantly inhibited retinal cell proliferation and promoted cell apoptosis. Furthermore, pretreatment with resveratrol can reduce alcohol‐induced retinal cell damage by activating the PI3K‐AKT signalling pathway.